BIM technology in greenhouse design and construction - KYYANOVSKYY, Oleksandr; CHEBANOV, Taras; CHERTKOV, Oleg; NOVAK, Tetjana; SLYEPTSOV, Yuriy; CHEBANOV, Leonid (Ways to Improve Construction Efficiency, 2025)
The classification of greenhouses is considered, taking into account architectural and structural features. Various types, parameters and schemes of structural and technological work are shown. It is noted that during the development of greenhouse projects, in addition to traditional sections, original ones are performed - systems for shading, supply and distribution of carbon dioxide, additional lighting, etc. The features of greenhouse design using BIM technologies are considered, which allows creating a three-dimensional parametric model of the object, which contains not only geometric, but also informational characteristics. This provides the ability to visualize future greenhouses and conservatories in 3D format, which increases the accuracy of architectural and engineering solutions; automatic generation of estimate documentation based on the specified parameters of materials, structures and equipment; simulation of operational processes (heat exchange, energy consumption, water supply, microclimate); modeling of the life cycle of the object, which makes it possible to take into account the costs not only for construction, but also for further operation. Automation of estimate calculations is synchronized with the use of BIM platforms (Autodesk Revit, ArchiCAD, Bentley Systems, etc.), which, in turn, allows you to form material specifications in real time, automatically update estimates when changes are made to the project, use national and international regulatory bases for calculating the cost of construction work, increase the transparency of financial planning and budget control. The main classification features of greenhouses are shown, examples of the application of original engineering solutions are given. The prospects for the development of technologies for the installation and reconstruction of greenhouses, taking into account energy efficiency and automation using building information technologies (BIM), are analyzed.